心臓線維芽細胞活性化に対するアブラナ属野菜由来 3,3‘-ジインドリルメタンの効果 - 斉藤, 麻希 (日本薬理学会年会要旨集, 2022)
Phytochemicals are bioactive substances produced by plants so as to protect them from infection by fungi, bacteria, and viruses. Nowadays, many scientists have focused on and reported their beneficial effects against the activation of inflammatory cells and/or various types of cancer cells. In the present study, I investigated the effects of 3,3'-diindolylmethane (DIM), an indole derivative contained in Brassica vegetables, on the activation of cardiac fibroblasts, which is deeply involved in cardiac fibrosis and furthermore it would cause heart failure.Human cardiac fibroblasts (hCF) were purchased and grew on collagen type I-coated culture dishes in the medium for hCF. The hCF were stimulated with 0.03~3 micro M of angiotensin II for 24 hrs present or absent of various concentrations of DIM. After the stimulation periods, the total RNA of the cells was conventionally extracted and then used for reverse transcription followed by real-time PCR.The stimulation with angiotensin II tended to increase the expression of connective tissue growth factor (CTGF), one of the indicators for fibroblast activation, and concomitant application with DIM seemed to suppress these increases. The expression levels of other molecules which seemed to be involved in the activation of the fibroblast, we investigated, had a similar tendency as CTGF. These results suggest that DIM has the potential to be a candidate compound for the alleviation of the progression of cardiac fibrosis.